If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + -3) + 2 = 3x + 3(-4 + x) Reorder the terms: 6(-3 + x) + 2 = 3x + 3(-4 + x) (-3 * 6 + x * 6) + 2 = 3x + 3(-4 + x) (-18 + 6x) + 2 = 3x + 3(-4 + x) Reorder the terms: -18 + 2 + 6x = 3x + 3(-4 + x) Combine like terms: -18 + 2 = -16 -16 + 6x = 3x + 3(-4 + x) -16 + 6x = 3x + (-4 * 3 + x * 3) -16 + 6x = 3x + (-12 + 3x) Reorder the terms: -16 + 6x = -12 + 3x + 3x Combine like terms: 3x + 3x = 6x -16 + 6x = -12 + 6x Add '-6x' to each side of the equation. -16 + 6x + -6x = -12 + 6x + -6x Combine like terms: 6x + -6x = 0 -16 + 0 = -12 + 6x + -6x -16 = -12 + 6x + -6x Combine like terms: 6x + -6x = 0 -16 = -12 + 0 -16 = -12 Solving -16 = -12 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 4+9g=22 | | -6(3x-8)=6.3 | | 7x+4=4x-25 | | r^2=57 | | x^2=(2*3)+3 | | 15-2x=x-14 | | -2x+38=x+15 | | 2(2x+3)=-4(x+1)-2 | | -4-12=13+x | | 6x-7=3x+25 | | 125m-100m+43200=45675-200m | | 2(x+4)=8x+5-6x+3 | | 2j^2-j-3=0 | | 4(-3y+5)+5y=13 | | x=283 | | x^2-x-12.01=0 | | 48x+8x= | | 4x+20=9x-4x | | 4b+5=29 | | 4x+20=9x-4y | | 10b^2-78b-16=0 | | x^2-x-11.99=0 | | 0.18x+0.02(y+4000)= | | 3(0)-2b=18 | | .20(x+12)=25 | | 4(6y+2)-6=-2 | | -8x-1.2=-7x-14.7 | | 16-48+4= | | 2(9+24)=30 | | -7+5(1+6x)=-39-7x | | .20(x-200)=160 | | 5x+3=48findx |